Estimation of subsurface flow hydrograph of catchments using time-area hydrograph method - Hossein Fariborzi; Mostafa Akbari Kheirabadi; Touraj Sabzevari; Andrea Petroselli; Mohsen Tarahi (Acta Scientiarum Polonorum. Formatio Circumiectus)
Aim of the study: In this study, a novel approach was undertaken, employing the concept of SSF isochrones in tandem with the time-area histogram (TAH) method as a fresh model for SSF estimation within catchments.